Child Marriage in Sukabumi West Java: Self and Agency of Girls - Grijns, Mies (Jurnal Perempuan, 2016)
What makes child marriage an option for girls and their relatives in this present time? How and why does it happen in an average village in Sukabumi, West Java? Kabupaten Sukabumi is one of the districts in West Java that has a high number of child marriages, especially in the villages in the periphery. The selected research village is not a child marriage hot-spot compared to provincial standards. With an incidence2 of 32 % for marriage under 18 of ever married women between 20-24 it is slightly higher than the provincial average of 30.7%3 . Compared to the Indonesian average of 17% for marriage under 18 it is much higher4 . The choice to do research in one village enables us to look in detail at different aspects of child marriage and intersectionality in the same setting. The research is based on 28 qualitative in-depth case-studies, combined with a census of all households with 20-24-year-old male and female members and supporting interviews and observations. Fieldwork is about to be finalised, other parts of the research are still ongoing. Sketches of six cases – five girls and one boy – show the diversity and complexity of child marriage. The article discusses the potential agency of young people vis-a-vis their parents/elders, from self-realised marriage to forced marriage. It confirms the role of common causes like the lack of control of girls’s sexuality and the fear of zina, and poor access to education and health when it comes to pregnancies, but questions the role of poverty as a direct reason of child marriage. Every case seems to be a particular combination of causes based on morality and religion, the composition of households, parental care and upbringing, the access girls have to formal and religious education, including sexual education, and to the local labour market. Gender and age are crosscutting hierarchies with girls at the most powerless side of the equation.